Strategic foresight of staffing needs of innovative development of socio-economic systems - Elena Okunkova (Управление)
The research has been conducted in order to develop theoretical and methodological approaches to forecasting the future needs of the innovative economy in personnel to ensure the demand for formed human resources capacity. Development of basic techniques and instruments of calculation of need of innovative economy for highly qualified personnel on long-term and medium-term prospects has been based on such methodological approaches as system, activity and competence-based approaches, situational approach, methodology of the interactive, understanding and interpretive sociology, methodology of synergy, network thinking and social management, methodology of the modal analysis. A number of methodological problems of the existing systems of providing innovative economy in a personnel has been revealed, described and systematized: the forecast of balance of a labor resources does not consider changes of working conditions, modernization of production assets and new technologies; planning of target figures of enrollment of students for master programs is performed in a separation from real personnel requirements; lack of criteria system of detection of competence-based requirements of innovative economy; the imminent need of transition from scenario approach of forecasting of needs of economy for professional staff to approach “a threefold spiral”. The article proposes a methodological approach to forecasting the staffing needs of the innovative economy, which makes a provision for creating strategic long-term and mid-term forecasts and their annual adjustment at the operating level using the technologies of strategic foresight. The decomposition has been carried out by the types of forecasts for such characteristics as: level of regulation, purpose, key definitions, methods and approaches, factors, types of information, tools for providing staffing needs at each level, the main results. Such approach will allow to reduce the state costs for staff coaching and to prevent “combustion” of competences unclaimed by future labor market. The model of interaction of the labor market and the sphere of professional education, based on a strategic foresight of personnel requirements, has been designed to provide the independent, reasonable professional choice of youth today for satisfaction and social mobility of the population in future. The implementation of the proposed approach will allow to increase the quality of forecasts of personnel needs of the innovative economy and to create the basis for scientifically sound regulation of the development of general, professional and additional education at the federal and regional levels. This, in turn, will contribute to achieve maximum compliance between the personnel needs of the innovative economy and its formed resource potential.